Development of an Antioxidant Phytoextract of Lantana grisebachii with Lymphoprotective Activity against In Vitro Arsenic Toxicity - Elio A. Soria; Patricia L. Quiroga; Claudia Albrecht; Sabina I. Ramos Elizagaray; Juan J. Cantero; Guillermina A. Bongiovanni (Hindawi Limited, 2014)
Phytochemicals have been presumed to possess prophylactic and curative properties in several pathologies, such as arsenic- (As-) induced immunosuppression. Our aim was to discover a lymphoprotective extract from Lantana grisebachii Stuck. (Verbenaceae) (LG). We assessed its bioactivity and chemical composition using cell-based assays. Fractions produced from a hexane extract acutely induced nitrite formation in T-activated cell cultures P<0.0001. Water extraction released a fraction lacking nitrite inducing activity in both lymphocyte types. Aqueous LG was found to be safe in proliferated and proliferating cells. The infusion-derived extract presented better antioxidant capacity in proportion to phenolic amount in lymphocytes (infusive LG-1i at 100 μg/mL), which protected them against in vitro As-induced lymphotoxicity P<0.0001. This infusive LG phytoextract contained 10.23±0.43 mg/g of phenolics, with 58.46% being flavonoids. Among the phenolics, the only predominant compound was 0.723 mg of chlorogenic acid per gram of dry plant, in addition to 10 unknown minor compounds. A fatty acid profile was assessed. It contained one-third of saturated fatty acids, one-third of ω9, followed by ω6 (~24%) and ω3 (~4%), and scarce ω7. Summing up, L. grisebachii was a source of bioactive and lymphoprotective compounds, which could counteract As-toxicity. This supports its phytomedical use and research in order to reduce As-related dysfunctions.